Factors That Influenced A Generation Z In Search Of Health Information On The Internet - Ice Marini; Koniasari Koniasari (Sean Institute, 2023)
Generation Z is a transitional generation from the previous generation and is also known as iGeneration, the net generation or internet generation. The age group of 18 – 24 years is the highest group in the use of online services with a minimum access of 1 time per month compared to other age groups. Research on adolescent sexual behavior (JHCCO-UGM in 2017) states that adolescents aged 15-19 years seek information about health from peers and the internet.The purpose of this study is to determine the factors that influence Generation Z in seeking health information through the internet. This study used a cross sectional study design with a total sample of 84 people and taken by accidental sampling. Data was collected by distributing questionnaires, the data were analyzed descriptively and used chi-square test. The results of the bivariate study showed that there was no relationship between gender (p=0.463), age (p=1,000) with searching health information via the internet, but there was a relationship between internet use (p=0.000), attitude (p=0.030) and knowledge (p= 0.000). The results of the multivariate test showed that knowledge had the most significant relationship with searching health information via the internet. There is a need for socialization to generation Z regarding health information and internet safety so that they can be more precise in using the internet as a medium for health information